Five-year retrospective study of HER2+ breast cancer in a referral hospital in the state of Amazonas - Silva, Lázara Gabriela Oliveira; Pereira, Hilka Flávia Barra do Espírito Santo Alves; Moraes, Daniel dos Santos; Amorim, Ligia Rebecca Mota; Castro, Luís Alexandre Lira de (Mastology, 2024)
Introduction: Breast carcinoma is considered the most common malignancy in women, with a high incidence in Brazil and in the North region, surpassed only by non-melanoma skin cancer and cervical cancer. The HER2+ molecular subtype tends to grow and spread more quickly than other subtypes, resulting in the second worst outcome, behind only the triple-negative subtype. Methods: This was a retrospective, descriptive epidemiological study, using data from the medical records of 192 patients with HER2+ breast cancer treated at the Fundação Centro de Controle de Oncologia do Amazonas (FCECON), from 2014 to 2018. Results: The mean age of patients was 52±12 years. The predominant origin was Manaus. AM (53.1%). The most common education level was complete secondary education (36.5%) and the occupation was self-employed (37%). Most diagnoses were made in 2014 (23.4%). Regarding staging, the most common ones were stages IIIA and IIIB, both 20.83%. Concerning treatment, all patients (100%) underwent radiotherapy and chemotherapy, and surgery in 80.2%, including mastectomy (58.33%) and quadrantectomy (21.87%). Local recurrence and distant metastasis were both found in 7.3% of patients. With respect to the outcome, patients in follow-up predominated (53.6%), while mortality rate was 0.5%. Conclusions: The series demonstrated that patients with HER2 breast cancer present advanced staging and undergo neoadjuvant chemotherapy and surgery. The center in the present study is an institution that receives patients from several municipalities in the countryside of Amazonas and other states, and thus, many patients with advanced stages are cared for, since many such cities have no resources to perform mammography, compromising screening.